Analyzing the Challenges and Barriers to Develop State Civil Apparatus Competency Through Talent Management Development After the Release of the National Succession Planning System - Sidabutar, Victor Tulus Pangapoi (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
Indonesia has transitioned from a public service management model to one to improve service delivery and competitiveness. However, this change faces challenges of efficiency in processes, human resource structures, and bureaucracy. Public distrust and State Civil Apparatus (ASN) non-compliance with the flow of reform pose challenges to increasing ASN competency and leadership reform. The implementation of breakthroughs in the development of public services still cannot prevent corruption both in regional and central government. Corruption does not only occur in the fiscal sector but also the ‘buying and selling’ positions due to the ASN’s low integrity. Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 38 of 2017 concerning Competency Standards for State Civil Apparatus Positions requires that a State Civil Apparatus must have technical, managerial, and socio-cultural competence, which is constrained by the application of rules related to functional positions and career development, the institutionalization of the ASN’ workplace, and development of ASN training institutions. These constraints influence the ASN’s desire to develop. Thus, an integrated succession planning system for competency development which involves public participation is needed to prevent corruption, collusion, and nepotism in its implementation.